Perceptions of Family Caregivers in the Caring for COVID-19 Patient: Self-Sacrificing Management, Fear, and Loneliness to Protect the Patient—A Qualitative Content Analysis. - Faghani, Safieh; Ahmadi, Fazlollah; Mohammadi, Eesa (Health & Social Care in the Community, 2023)
This study aimed to evaluate the perception of family caregivers in the care process of patients with COVID-19. This study was conducted on 19 family caregivers, who were selected using purposive sampling from 2021 to 2022. Unstructured interviews were used to collect data. The data were analyzed using the Kyngas conventional content analysis approach. The analysis of data led to three main themes, including unremitting efforts in physical care in the light of traditional medicine, accuracy, and intelligence in psychological attention and trying to maintain environmental health. According to the results, family caregivers provide high levels of self-sacrificing, continuous, and comprehensive, combined with fear and loneliness care in different dimensions with little or no support from the family, community, and health team.